A Prospective Study to Investigate the Effect of Fesoterodine Treatment on Quality of Life, Anxiety, and Depression in Urge-Type Urinary Incontinence: Quality of life, mood disorders and urinary incontinence - Aksak, Arif; Çakmak, Güzin; Öztürk, Zeynel Abidin (Urology Journal, 2021)
Purpose: Urinary incontinence (UI) is a fundamental health problem, can occur at any age but is especially common in older women. Depression and anxiety are also considerable problems for the elderly. UI is one of the geriatric syndromes that are thought to be related to depression and quality of life (QOL). Materials and methods: This prospective study was conducted for a period of 2 months from February 2020 to April 2020. Women who applied to the outpatient clinic of geriatrics with UI symptoms were taken into the study. The type of UI was determined by using the 3 Incontinence Questions (3IQ). Only patients with urge incontinence were included in the study. Patients were evaluated for QOL, anxiety, depression, disability, and geriatric syndromes before and after treatment. Data analysis was done by using SPSS version 22. Results: The study population was 42 women; the mean age was 69.7 +/- 4.3 years. QoL, anxiety, and depression symptoms, and ADL were revealed to be improved after treatment. ICIQ-SF, I-QOL, and HADs scores were associated with UI treatment when evaluated with one-way MANOVA (F [4, 79] =3.25, p=0.00, Wilk’s Λ=0.859, partial η2=0.14). Conclusion: UI is a common problem in the elderly. Patients usually hesitate to tell this complaint to even doctors. That situation affects their physical and psychological condition negatively. In this study, we reached that anticholinergic treatment (fesoterodine) improved ADL, QoL, and psychological symptoms. Those findings represented us that proper treatment of UI is critical for healthy aging.